If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + 2 + -3 + -16 = 0 Reorder the terms: 2 + -3 + -16 + s = 0 Combine like terms: 2 + -3 = -1 -1 + -16 + s = 0 Combine like terms: -1 + -16 = -17 -17 + s = 0 Solving -17 + s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + s = 0 + 17 Combine like terms: -17 + 17 = 0 0 + s = 0 + 17 s = 0 + 17 Combine like terms: 0 + 17 = 17 s = 17 Simplifying s = 17
| 80=3x+19 | | 22+8x=-5+3(5x-5) | | -2(a-5)=27-2a | | 20(x-1)=-4(5-x)+16x | | y^2+11y-12=0 | | 12y^2-4y^4= | | 4x-2(x-7)=4 | | 6x^2+5x-8=-4 | | 43+63+57+4x=55 | | .18y+.04(y+6000)=1780 | | us+uz=t | | 7n=85n | | 2r-(-4+r)=7-2r | | 32y+5y=2 | | 6x-12+2x=7+8x-19 | | 7x+1x=3x+3 | | 5x(x)-13x+6=0 | | 2x+3(x+1)=13 | | 24x^2+76x+60=0 | | 3(2x-5y)=30 | | w-3=2w+5 | | -(3x+1)+2(1-2x)=-13 | | -5x-4=-2x+8 | | 2(3/8)= | | 61=6-8x-3 | | -10n+3(8+8n)=-6(m-4) | | (-19)-13= | | -4(2+3b)=8-4b | | -6(-8+v)=162 | | 1.5+4x=x+10 | | 7-3x+x=15 | | 16x^2+24x+7=0 |